Parameterized Unit Testing with Pex (Tutorial) - Tillmann, Nikolai; Halleux, Jonathan "Peli" de (Proc. of Tests and Proofs (TAP'08), 2008)
This hands-on tutorial will teach the principles of Parameterized Unit Testing [5,4] with Pex [2], an automatic test input generator for .NET which performs a systematic program analysis, similar to path bounded model-checking. A parameterized unit test is simply a method that takes parameters, calls the code under test, and states assertions.